Students' Perception of Listening Materials at University - Suharti Siradjuddin; Muhammad Yahrif (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The aims of this study are to assess students’ perception of listening materials used in the listening class of the English education program at the Megarezky University of Makassar.  Students' perception of the use of listening materials is beneficial in order to understand and improve listening material especially in the English education program at the Megarezky University of Makassar. This researcher was used a qualitative approach to collect data through questionnaires and interviews. The participants of this research were 10 students of the English education program in the 2020/2021 academic year. The technique of analysis covers students' perception related to the general perception of listening material that they received in the first and second semester in listening courses. The finding indicated students have positive opinions of the listening materials used in class. However, there were some positive feedbacks and some potential problems with the use of listening materials. All these perceptions of the listening materials can imply the improvement of better listening materials in the future.